A precorrection study: effects of step reduction for high school students with emotional and behavior disorders in the classroom - White, Sherry A. (Kansas State University, 2019)
A precorrection is an antecedent-based instructional approach designed to reduce problem behavior before it occurs. Colvin, Sugai, and Patching (1993) outlined seven steps as part of precorrection strategy. The purpose of this study is to determine if two of the seven steps are necessary components of the intervention package to reduce externalizing problem behaviors for students at-risk for or with an emotional behavioral disorder (EBD) in a less restrictive environment to include the general education setting and uses an alternating-treatments design to examine the outcomes in step reduction of contextual factors and reinforcement to reduce externalizing behaviors. The study participants are comprised of three high-school students identified at-risk or with EBD, who attend classes in a less restrictive classroom. The intervention results indicated that all seven-steps of a precorrection strategy to include without contextual factors and without reinforcement are not necessary to reduce externalizing behaviors. This study outlines variability of results related to specific intervention packages and academic engagement for individual students.
Keywords: Precorrection Strategy; Antecedent-based intervention; Tier-2 intervention; step reduction study; Students at-risk; emotional behavioral disorders (EBD)